"A Whole Bunch of Love the Sinner Hate the Sin": LGBTQ Microaggressions Experienced in Religious and Spiritual Context. Issue 10 (24th August 2019) - Lomash, Edward F.; Brown, Tabria D.; Paz Galupo, M.
ABSTRACT: Research on microaggressions experienced by LGBTQ people has focused largely on a general understanding of this concept; however, no research exists that focuses exclusively on microaggressions that LGBTQ people face across religious and spiritual communities. The present study addressed this gap in the literature by using a qualitative method to allow LGBTQ people ( N = 90) to directly report microaggressions that they have experienced within their religious and spiritual communities. Thematic analysis revealed three predominant themes: (1) LGBTQ identities as inauthentic; (2) religious/spiritual tolerance of LGBTQ Identities, and (3) LGBTQ and religious/spiritual identities as incompatible. Implications and future directions discussed.